[English original] Isokinetic evaluation and treatment in the postoperative period of rotator cuff disease: a case report - Silva, Pedro Afonso Cazarin (2026)
INTRODUCTION: Even with a successful surgical procedure to repair the rotator cuff (RC), immobilization, pain, or muscle atrophy can lead to dysfunction and reduced RC strength, PURPOSE: This study sought to analyze the effects of physiotherapy through isokinetic exercises in these dysfunctions. METHODOLOGY: This is a case report of a 60-year-old male patient diagnosed with subluxation of the humeral head, and full-thickness tear of the supraspinatus tendon, with laceration, and tendinous retraction of approximately 2.4 cm. The patient underwent an open RC repair. After the failure of conventional physiotherapy, the individual was treated with isokinetic exercises. Functional status was evaluated using the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire and an isokinetic dynamometer was used to evaluate muscle performance in concentric mode, at velocities of 60, 180, and 300 º/s, in flexion/extension and internal/external shoulder rotation movements. The minimum clinically important difference for functional status was reached. RESULTS: The peak torque (PT) for flexors showed improvement at all velocities; the extensor muscles improved only at 180 °/s. The external rotators showed an enhancement in the PT at 60 and 300 º/s. The agonist/antagonist ratio of extensors/flexors at 60 and 300 º/s showed percentages of improvement above 30 %. For internal/external rotators, the PT results also showed improvements in all velocities. CONCLUSION: In this case study, the isokinetic exercises prescribed in the postoperative period, after an open RC repair, resulted in a positive effect on the recovery of functional status and muscle performance.